Hypochloraemia in Patients with Heart Failure: Causes and Consequences - Cuthbert, Joseph J. (Cardiol Ther, 2020)
Hypochloraemia is a common electrolyte abnormality in patients with heart failure (HF). It has a strong association with adverse outcome regardless of HF phenotype and independent of other prognostic markers. How hypochloraemia develops in a patient with HF and how it might influence outcome are not clear, and in this review we explore the possible mechanisms. Patients with HF and hypochloraemia almost invariably take higher doses of loop diuretic than patients with normal chloride levels. However, renal chloride and bicarbonate homeostasis are closely linked, and the latter may be influenced by neurohormonal activation: it is likely that the etiology of hypochloraemia in patients with HF is multifactorial and due to more than just diuretic-induced urinary losses. There are multiple proposed mechanisms by which low chloride concentrations may lead to an adverse outcome in patients with HF: by increasing renin release; by a stimulatory effect on the with-no-lysine kinases which might increase renal sodium-chloride co-transporter activity; and by an adverse effect on myocardial conduction and contractility. None of these proposed mechanisms are proven in humans with HF. However, if true, it might suggest that hypochloraemia is a therapeutic target that might be amenable to treatment with acetazolamide or chloride supplementation.